Anomalies Dynamic Analysis and Correction Software - Pogossian , Edward; Grigoryan , Arthur (Mathematical Problems of Computer Science, 2021)
The research is aimed to develop an effective Anomalies Dynamic Analysis and Correction Software (ADACS) for Grid Armenia. A software is developed that in addition to predetermined and fixed forms of protection of variety of servers generates game trees of possible anomalies and elaborates recommendations to avoid them by analyzing possible strategies throughout the game trees and searching the best correction strategies. Experiments on correction of anomalies in overfilling the memory of the cluster of IPIA are processed.